Experience in Treating Patients with Acute Sigmoid Colon Obstruction (Experimental and clinical study) - Ten Dmitry Olegovich (Genius Journals, 2022)
The experimental – clinic investigations of the improvement methods are carried into colon intestine anastomosis for putting sutures.Experiments are did with 30 no sort, male and female dogs, weight 15-20 kg. For anesthesia is used Tiopental natrium 5-6 mg/kg. In the first stage provided simulation of acute intestinal impassibility, in the second stage occurred surgical treatment, which using resection colon as well as colon intestinal anastomosis with different suture materials. Than these operated dogs observed during 3 months. Conclusion got in the 7, 14, 20 days on each month and become morphological researches.In clinic observed 165 patients with intestinal impassibility. All patients divided 2 groups, who carried several types of surgical methods in colon and sigmoidal intestines. Patients observed during the 6 years.At the end can conclude that our methods do not get postoperation complications (failure of anastomosis, stenosis and other), easy using, and unrequired costly instruments, can carry in every surgical departments.
Keywords: Acute Intestinal Obstruction; Anastomosis; Intestinal Resection; Large Intestine